ASSESSMENT OF TEACHERS’ LEVEL OF LITERACY AND ATTITUDE TOWARDS ICT APPLICATION IN VOCATIONAL AND BUSINESS EDUCATION - Adetayo, Janet Oyebola (Sokoto Educational Review, 2012)
The study assessed teachers’ level of literacy and attitude towards ICT Application in Vocational and Business Education. In carrying out this survey study a sample of four hundred (400) vocational and business education-related subject teachers were selected from all the four divisions in Ogun State of Nigeria. Three research questions were raised and answered. Frequency count and simple percentages were the analytical tools used for the analysis of data collected. The results showed that computer as an ICT facility is not adequately available in schools, majority of the teachers have low literacy level in the use of computer and that teachers are favourably disposed to the use of ICT facilities in teaching. The study among others, therefore, recommended that the Government should make computer and other ICT facilities readily and adequately available in schools.